Soybean Endo-1,3-Beta-Glucanase (GmGLU) Interaction With Soybean mosaic virus-Encoded P3 Protein May Contribute to the Intercelluar Movement - Shi, Feifei; Wang, Ying; Zhang, Fang; Yuan, Xingxing; Chen, Huatao; Chen, Xuehao; Chen, Xin; Cui, Xiaoyan (Frontiers in Genetics, 2020)
Soybean mosaic virus (SMV), a member of the Potyvirus genus, is a prevalent and devastating viral pathogen in soybean-growing regions worldwide. Potyviral cell-to-cell movement was shown to target plasmodesmata (PD) by CI with the help of P3N-PIPO in a ratio-dependent manner. Potyvirus-encoded P3 is reported to participate in virus replication, movements, and pathogenesis. This study provides evidence that the soybean (Glycine max) endo-1,3-beta-glucanase protein (designated as GmGLU) interacts with SMV-P3 by using a two-hybrid yeast system to screen a soybean cDNA library. A bimolecular fluorescence complementation assay further confirmed the interaction, which occurred on the cytomembrane in Nicotiana benthamiana cells. Subcellular localization experiment indicated that GmGLU localized in the cytomembrane and GmGLU with PD (plasmodesmata) marker co-localization at plasmodesmata site. The transient expression of GmGLU can promote the coupling of Turnip mosaic virus replication and cell-to-cell movement in N. benthamiana. Meanwhile, qRT-PCR experiment demonstrated that the expression of GmGLU increased under SMV infection, which involved in regulation of callose. Under SMV infection, Callose deposition at PD was observed obviously by staining with aniline blue, which raise a physical barrier restricting cell-to-cell movement of SMV. While overexpression the GmGLU into the leaves under SMV infection, the callose induced by SMV was degraded. When coexpression the GmGLU and SMV in Soybean leaves, callose was not found, whereas a large amount of callose deposition on soybean leaves which were only under SMV infection. The results show that GmGLU can degrade the callose induced by SMV infection and indicate that the interaction between the membrane protein SMV-P3 and GmGLU contributes to the potyvirus intercelluar movement, and GmGLU may be an essential host factor involvement in potyvirus infection.